2014
DOI: 10.1016/j.chb.2014.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Does country context matter? Investigating the predictors of teen sexting across Europe

Abstract: Despite growing research interest in sexting, not much is known about individual and country differences in engaging in sexting. Therefore, the aims of this study were to investigate (a) which individual and country characteristics explain sexting and (b) whether individual predictors vary across countries. On the individual level, we investigated age, gender, sensation seeking, and internet use. On the country level, we investigated traditionalism, gross domestic product, and broadband internet penetration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
12

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 41 publications
9
69
1
12
Order By: Relevance
“…Dake, et al, 2012;Lenhart, 2009;Rice et al, 2014), while others found a higher frequency among boys (Dowdell, Burgess, & Flores, 2011) and vice versa National Campaign to Prevent Teen and Unplanned Pregnancy & CosmoGirl.com, 2008). Data from the EU Kids Online Project showed that in Sweden boys sent and posted sexual pictures slightly more than girls, 12.9% vs. 10.2% (Baumgartner et al, 2014), while the studies from Ungdomsstyrelsen (2009; indicated that girls posted sexual pictures more often than boys (6.2 % vs. 4.0%).…”
Section: Socio-demography and Psychosocial Healthmentioning
confidence: 99%
See 3 more Smart Citations
“…Dake, et al, 2012;Lenhart, 2009;Rice et al, 2014), while others found a higher frequency among boys (Dowdell, Burgess, & Flores, 2011) and vice versa National Campaign to Prevent Teen and Unplanned Pregnancy & CosmoGirl.com, 2008). Data from the EU Kids Online Project showed that in Sweden boys sent and posted sexual pictures slightly more than girls, 12.9% vs. 10.2% (Baumgartner et al, 2014), while the studies from Ungdomsstyrelsen (2009; indicated that girls posted sexual pictures more often than boys (6.2 % vs. 4.0%).…”
Section: Socio-demography and Psychosocial Healthmentioning
confidence: 99%
“…A majority of youth have a positive attitude to sexuality, are happy about their sex life and most of the sexual experiences are positive (Häggström-Nordin et al, 2005;Rogala & Tydén, 2003;Tydén, & Rogala, 2004). Sweden and the Scandinavian countries are seen as one of the most gender equal countries in Europe along with fostering one of the most permissive sexual attitudes (Arnett & Balle-Jenssen, 1993;Baumgartner, Sumter, Peter, Valkenburg and Livingstone, 2014;Widmer, Treas, & Newcomb, 1998). The differences between Sweden and for example the US in terms of gender equality and attitudes toward sexuality are larger than between Sweden and other European countries.…”
Section: Sexual Health Within the Swedish Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…However, not much is known about adolescents' underlying perceptions and reflections toward sex-related online behaviors that may explain such differential engagement patterns. Moreover, these perceptions and reflections may also vary by nation and culture (Baumgartner, Sumter, Peter, Valkenburg, & Livingstone, 2014;Brugman, Caron, & Rademakers, 2010). To our knowledge, no qualitative studies have investigated Dutch adolescents' motives, perceptions, and reflections toward sex-related Internet use.…”
mentioning
confidence: 99%